Basics of Organization, Culture and Organizational Behavior in Islamic Perspective - Fitri Amelia (Konsultan Jurnal Ilmiah Indonesia, 2024)
In an organization, resources are needed to achieve the specified goals, this is an important factor. A successful organization has a strong organizational culture so that it is able to attract, maintain and reward anyone who fulfills obligations and achieves targets. This study focuses on the study of the Basics of Organization, Culture and Organizational Behavior in an Islamic Perspective. The method in this study uses literature studies. The technique used in collecting data in this study is documentation. The technique in analyzing this research data uses a descriptive analytical type. The results of this study are that this organizational culture theory is a theory that has an important influence on theory and research in the field of organizational communication. The behavior of each individual in the organization is directed at the desired goals. So a behavior in the organization and the ability of leaders to lead an organization, especially in educational institutions.